Translating national policy to improve environmental conditions impacting public health through community planning - Fiedler, Beth Ann (Springer, 2018)
This first-of-its-kind volume traces rarely explored links between public policy, the state of the environment, and key issues in public health, with recommendations for addressing longstanding intractable problems. Experts across diverse professions use their wide knowledge and experience to discuss hunger and food sustainability, land use, chronic and communicable diseases, child mortality, and global water quality. Interventions described are varied as well, from green technology breakthroughs to regulatory accountability, innovative urban planning and community policing programs.